Application of abscisic acid (S-ABA) at different stages of ripening on color development of ‘Rubi’ table grape - Ribeiro, Luana Tainá Machado (2022)
The color of the berries is an important aspect of the quality of table grapes and crucial for marketing. The ‘Rubi’ table grapes grown in the subtropical climate generally lack color intensity due to the inhibition of anthocyanins by high temperatures during ripening. The exogenous application of abscisic acid (S-ABA) can be used to overcome this problem as the accumulation of anthocyanins in the berry skin is regulated by this plant growth regulator. The objective of this study was to assess the effect of the exogenous application of S-ABA at different stages of ripening on color development in ‘Rubi’ table grapes using the soluble solids (SS) content as a marker of ripening. The study was conducted during two seasons in commercial vineyards. The first trial was conducted in Marialva, Parana, Brazil, during the 2019 summer season crop (harvest in December). S-ABA (400 mg L-1) was exogenously applied at different stages of ripening of ‘Rubi’ table grapes (determined by the SS content of the berries): control (without application); SS = 8-9 ºBrix; SS = 10-11 ºBrix; SS = 8-9 ºBrix (two applications; the second one applied 10 days after the first); and SS = 10-11 ºBrix (two applications; the second one applied 10 days after the first). The second trial was conducted in Cambira, Parana, Brazil, during the 2020 off-season crop (harvest in May). S-ABA (400 mg L-1) was exogenously applied at different stages of ripening of Rubi grapes: control (without application); SS = 6-7 ºBrix; SS = 7-8 ºBrix; SS = 9-10 ºBrix; SS = 6-7 ºBrix (two applications; the second one applied 14 days after the first); SS = 7-8 ºBrix (two applications; the second one applied 14 days after the first); and SS = 9-10 ºBrix (two applications; the second one applied 14 days after the first). A randomized block design was used as the statistical model with four replications, and each plot consisted of one vine. The variables analyzed were total anthocyanin contents, color index (CIRG), and color attributes (L*, C*, h°, and deltaE) of berry skin. The total anthocyanin accumulation and color attributes of the berries were evaluated every 10 and 7 days after the first application of S-ABA until harvest in the first and second trials, respectively, and the other variables were evaluated at harvest. In the summer-season crop, when the SS content was 8-11 ºBrix, the application of S-ABA increased the concentration of the total anthocyanins 4 times compared to that in the control, improving berry color development. Furthermore, in the off-season crop, when the SS content was 6-10 ºBrix, the application of S-ABA increased the concentration of total anthocyanins 2-3 times compared to that in the control, improving the color attributes of berries. In both crops, a single application of the plant growth regulator was sufficient to intensify the color of the berries.